The extent of adjustment problems of foreign students in four selected schools in the Philippines - Fry, Marion Brendlinger 1935- (s.n.], 1973)
The extent of the adjustment problems of the foreign students enrolled in schools in the Philippines, namely, Brent School in Baguio, Cebu American School in Cebu, and Dole Philippines Elementary School in Makati, Rizal was determined in this study.